Spatial and temporal relations between the barred warbler Sylvia nisoria and the red-backed shrike Lanius collurio in the Wielkopolska region (W Poland) - Kuźniak, Stanisław (1933– ); Bednorz, Jan ( –2013); Tryjanowski, Piotr (Muzeum i Instytut Zoologii PAN, 2001)
The Red-backed Shrike and the Barred Warbler are a pair of species engaged in breeding association. Whilst the arrival time of both species from their wintering grounds was not correlated, they differed in median arrival time by only one day. The majority of the Barred Warbler territories were located within those of the Red-backed Shrike, in both forest and farmland plots. The two species differed significantly in their selection of nest sites, at least in farmland. Unlike the Red-backed Shrike (n = 297), the Barred Warbler (n = 60) preferred blackberry bushes and small deciduous thornless shrubs, and avoided elder, conifers and hawthorn. The Barred Warbler nests were placed significantly lower than those of the Red-backed Shrike. The results show that no special ecological relationships exist as was suggested in earlier papers for other areas.
Bibliogr. p. 132-133
P. [129]-133 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Red-backed Shrike; Barred Warbler; Poland; Wielkopolska; Great Poland (region); Wielkopolski Park Narodowy; Leszno; nest sites; phenology; shrikes; birds; Lanius collurio; Laniidae; Sylvia nisoria; Sylviidae; Aves

Differences between the spring and autumn migration of the red-backed shrike Lanius collurio: record from the Eilat stopover (Israel) - Tryjanowski, Piotr; Yosef, Reuven (Muzeum i Instytut Zoologii PAN, 2002)
Migratory Red-backed Shrikes were mist-netted during the spring and autumn migrations (n = 1031 individuals) from 1984 to 2001 in Eilat (Israel). In a similar pattern of trapping, more than four times as many shrikes were caught during autumn than in spring. Males migrated significantly earlier than females in spring but not during the autumn migration, which suggests that in males there is a stronger drive to reach their breeding territories early. In both seasons and between both sexes we did not find any significant relations between the body measurements of individuals and the time of passage. The spring migration lasted a much shorter time than the autumn one. This was expressed by the minimum stopover duration, as well as by the time when Red-backed Shrikes occurred in Eilat. There are significant differences between wing chord length, body mass and fat scores between seasons. In autumn, males had longer wings, and both sexes were heavier and in better condition than in spring. The data suggest that the differences are an adaptation to their having to cross the Sahara Desert. The birds spend a statistically significantly shorter period of time at the Eilat stopover site in spring than in autumn (median 1 ą 1.5 days vs 5 ą 6.5 days). In autumn, recaptured birds were 6.3% heavier than during the first capture. The change in body mass was significantly correlated to the duration of the stopover. The results suggest that migration over desert is energetically costly and that Eilat is a very important stopover site for migrating Red-backed Shrikes.
Bibliogr. p. 89-90
P. [85]-90 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Red-backed Shrike; birds; bird migration; Israel; Red Sea coast; body condition; migration strategy; shrikes; Lanius collurio; Laniidae; Aves; 1984-2001

Food of the red-backed shrike Lanius collurio: a comparison of three methods of diet analysis - Tryjanowski, Piotr; Karg, Małgorzata K.; Karg, Jerzy (Museum & Institute of Zoology, 2003)
The diet of the Red-backed Shrike (Lanius collurio) was analysed from collars in nestlings, pellets and prey remains in larders. All the material was collected from the same territories in western Poland.A total of 2855 prey items were identified from all the samples. Insects, mainly Coleoptera, Hymenoptera and Orthoptera, constituted 98.9% of all the prey items identified.In order to determine the diet and predict the impact of food resources on Red-backed Shrike populations, three methods should be used together: pellet content analyses, collar sampling and larder analysis. Our findings suggest that pellet content analysis is an easy and non-invasive method for estimating prey diversity and the frequency index. However, collars are necessary to determine nestling diets. Analyses of prey remains in larders should be used to find large prey, handled before consumption. In a more advanced geographical analysis of the content of the shrike diet, we suggest pooling the data obtained by different methods from the same place, and/or carefully assign methods of diet analyses.
Bibliogr. p. 61-62
P. [59]-63 : ill. ; 27 cm
Streszcz. pol.
Abstract in Polish
Keywords: Red-backed Shrike; birds; nutrition; Poland; Wielkopolska; Great Poland (region); Turew; diet analysis; methods; shrikes; Lanius collurio; Laniidae; Aves; 1999-2000

Breeding biology of the great grey shrike Lanius excubitor in W Poland - Antczak, Marcin; Hromada Martin; Grzybek Jerzy; Tryjanowski Piotr; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum & Institute of Zoology, 2004)
A Great Grey Shrike population was studied in two large plots (220 km2 and 176 km2) in western Poland in 1999 - 2003. During the study period densities varied from 11.4 to 14.1 breeding pairs/100 km2 but numbers were stable. In all, 180 Great Grey Shrike nests were found - 114 (63.3%) in conifers, 66 (36.7%) in deciduous trees. This populations reproductive parameters were relatively high in comparison to those of other European populations: mean clutch size - 6.6, hatching success - 92.5%, mean brood size - 5.72, mean number of fledglings per pair - 4.1, mean number of fledged young per successful pair - 5.25. Eggs (mean 27.1 x 19.9 mm) were found to be larger than reported in the literature. Nesting success was similar in both study plots, but there was slight seasonal variability: 52.6% - 41.0% from 99 nesting attempts in the first plot, 43.7% - 42.1% from 37 nests in the second. Predation was the main cause of nest losses. Plastic string used as nesting material appeared to be the most important cause of partial failures: 13 (8.2%) of a total of 147 nestlings surviving to fledging perished as a result of becoming tangled up in it. Nestlings rarely starved. Nests in linear habitats suffered significantly higher breeding losses (78.6%, N = 28) than those in non-linear habitats (50%, N = 90). The high fitness values obtained from this population were probably due to traditional farming practices, the sparing use of pesticides and the good potential food base.
Bibliogr. p. 13-14
p. [9]-14 : ill. ; 27 cm
Abstract. pol.
Keywords: Great Grey Shrike; Lanius excubitor; breeding biology; farmland; nest location

Breeding ecology of the Red-Backed Shrike Lanius collurio in the Wielkopolska region (Western Poland) - Kuźniak, Stanisław (1933– ) (Instytut Zoologii PAN, 1991)
Bibliogr. p. 81-82
P. 67-83 : ill. ; 24 cm
Abstract in English, Polish. Taxa in Latin
Keywords: Red-backed Shrike; breeding biology; Poland; Leszno; shrikes; birds; Lanius collurio; Laniidae; Aves

O pożywieniu gąsiorka, Lanius collurio L., w okolicy Gniezna (woj. poznańskie) - Mielewczyk, Stefan (1933–2005) (Państwowe Wydawnictwo Naukowe, 1967)
Liczbowanie stron również: 157-175
Z 3 tabelami, 1 wykresem i 3 fotografiami w tekście
Bibliogr. p. 16-17 (172-173)
19 p. : ill. ; 24 cm
Abstracts in Russian, English. Nazwy taksonów także w jęz. łac.
Keywords: red-backed shrike; Poland; food; Gniezno; shrikes; birds; Lanius collurio; Laniidae; Aves

The composition and dynamics of a wintering bird community in an agricultural area of western Poland - Tryjanowski, Piotr (Muzeum i Instytut Zoologii PAN, 1995)
Bibliogr. p. 159-160
P. [153]-160 : ill., ; 24 cm
Abstract in Polish. Taxa in Latin
Keywords: birds; wintering; Poland, Western; bird communities; agricultural landscape; farmland; composition; dynamic; Aves

Remarks on ethology of the Red-backed Shrike, Lanius collurio L. - nest defence and nest desertion - Gotzman, Jerzy ( –2004) (Państwowe Wydawnictwo Naukowe, 1967)
Liczbowanie stron również: 83-96
With 4 diagrams in text
Bibliogr. p. 92-93
14 p. : ill. ; 24 cm
Abstracts in Polish, Russian. Nazwy taksonów także w jęz. łac.
Keywords: red-backed shrike; behaviour; experiments; nest defence; nest desertion; ethology; shrikes; birds; Lanius collurio; Laniidae; Aves

Obserwacje biologiczno-morfologiczne Lanius minor Gm., L. senator L. i L. collurio L. (Laniidae) w Janówce pod Tłuszczem - Feliksiak, Stanisław (1906–1992) (Państwowe Wydawnictwo Naukowe, 1976)
Liczbowanie stron również: 1-22
Z 3 tabelami i 2 fotografiami w tekście
ISBN tomu: 83-01-05102-7
Bibliogr. p. 18-19
22 p. ; 24 cm
Keywords: Lesser Grey Shrike; Woodchat Shrike; Red-backed Shrike; morphology; Tłuszcz; Poland; biological and morphological observation; shrikes; birds; Lanius minor; Lanius senator; Lanius collurio; Laniidae; Aves

2. międzynarodowe sympozjum na temat dzierzb (Ejlat, Izrael, 17-23 III 1996 r.) - Diehl, Barbara (Oficyna Wydawnicza Instytut Ekologii PAN, 1996)
Pages 204-206 ; 24 cm
Keywords: shrikes; congresses; Laniidae

A survey of the bearded tit Panurus biarmicus during the non-breeding season in a landscape of western Poland - Surmacki, Adrian; Stępniewski, Janusz (Museum & Institute of Zoology, 2003)
The population of Bearded Tit was studied on a 1872 km2 study area of predominantly agricultural landscape in W Poland, near Poznań. During the non-breeding period (October-March) surveys were made every 10-14 days on a sample of 44 marshlands selected at random out of 240 suitable habitat patches found in the study area. Bearded Tits were found at least once in 66% of the patches surveyed, but the average percentage of patches occupied per single survey was 25% and did not vary across the non-breeding season. Re-occupancy of individual reed-bed patches in successive surveys averaged 54% and was lowest during early autumn and in the second half of the winter. 39% of the sites occupied during the winter were used as breeding sites in the spring following or preceding the survey. Of 17 breeding sites, 16 were used by Bearded Tits also outside the breeding season. The numbers of birds recorded peaked in second half of October and declined thereafter. Flock size averaged 3.1 (range 1-55) birds and correlated with total number of Bearded Tits recorded during the single survey. Birds mostly foraged on reed seeds taken from reed ears. Foraging on the ground occurred mostly at the beginning and at the end of non-breeding season. Searching for invertebrates peaked in December-January.
Bibliogr. p. 57-58
P. [53]-58 : ill. ; 27 cm
Abstract in Polish
Keywords: Bearded Tit; birds; Great Poland (region); Poland; Wielkopolska; non-breeding season; foraging; reedbeds; parrotbills; Panurus biarmicus; Paradoxornithidae; Aves; 2000-2001

The breeding ecology of the greenfinch Carduelis chloris in urban conditions (study in Krotoszyn, W Poland) - Kosiński, Ziemowit (Muzeum i Instytut Zoologii PAN, 2001)
Data were collected in a medium-sized town. During five years 342 nests were found. The densities of breeding pairs varied over this period between 4.5 and 5.9 p/10 ha. The distribution of breeding pairs was uneven throughout the study area. The preferred nest sites were roadside trees, where 88.9% of the nests were built. The mean onset of egg-laying was 22 April (range 19-26 April). There was a tendency to start breeding earlier in warmer springs. The mean clutch size was 5.07 ą 0.74. There was a positive correlation between clutch size and the date of egg-laying. These data suggest that there was a compromise between the tendency towards earlier breeding and clutch size. In the study area the Greenfinch is a double-brooded species. Unlike other studies it was noted that the average clutch size increased in the second half of the breeding season. The maximum clutch size coincides with the second or replacement clutches. Hatching, fledging and breeding success were lowest when clutch sizes were largest. The nesting success estimated with the Mayfield and the "traditional" method was approximately similar (0.40 and 0.44 respectively). Cats and mustelids were probably the cause of most breeding failures. Corvids were not responsible for nesting failures.
Bibliogr. p. 119-120
P. [111]-121 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Greenfinch; breeding biology; Poland; Krotoszyn; nesting success; breeding success; timing of breeding; nest sites; clutch size; finches; birds; Carduelis chloris; Fringillidae; Aves

Badania ilościowe awifauny lęgowej w rolniczym krajobrazie kulturowym Wielkopolski - Kuźniak, Stanisław (1933– ) (Państwowe Wydawnictwo Naukowe, 1978)
Liczb. s. również: 423-450
Z 16 tabelami w tekście
ISBN tomu: 83-01-05102-7
Bibliogr. p. 23-24 (445-446)
28 p. ; 24 cm
Keywords: breeding birds; Poland; Greater Poland; Wielkopolska; quantitative studies; agricultural landscape; birds; Aves

Zgrupowania i wybiórczość siedliskowa ptaków wodnych na jeziorach Ziemi Lubuskiej w okresie jesiennym - Jermaczek, Andrzej (1957– ) (Państwowe Wydawnictwo Naukowe, 1987)
Bibliogr. p. 213
P. 197-214. : ill. ; 24 cm
Abstract in English, Russian. Taxa in Latin
Keywords: water birds; Poland; Lubusz Land; habitat selection; lakes; autumn; bird communities; birds; Aves

Ptaki naszych gór - Domaniewski, Janusz (1891–1954) (nakł. Księgarni św. Wojciecha, 1930)
W serii gł.: nr 227
62, [2] p., [19] p. of plates. ; 17 cm
Keywords: Aves; birds; birds - Poland

Breeding communities of birds in mid-field afforested areas - Gromadzki, Maciej (Państwowe Wydawnictwo Naukowe, 1970)
In mid-field afforested areas 44 bird species were found to nest. 18 of these species appeared to be typical to this habitat, representing 60-90% of the total number of birds of a community. Although in small afforested areas fewer species nest than in the large ones, the total population density there is higher. Species that feed in fields are more abundant in small afforested areas than in large ones. Their breeding territories are small. Only a slight relationship is seen between the size of an afforested area and the population density of those species which feed in it. The breeding territories of this group of birds are large, spreading along the afforested areas.
Pages 307-350 : illustrations ; 24 cm
Bibliographical references (pages 345-348)
Abstract in Polish
Keywords: birds; breeding birds; ecology; breeding biology; Poland; Kościan (region); Aves

Effects of lake morphometry, emergent vegetation and shore habitat on breeding bird communities - Kosiński, Ziemowit (Muzeum i Instytut Zoologii PAN, 1999)
The aim of this study was to investigate the role of lake morphometry, emergent vegetation and the surrounding habitat on breeding bird communities. The analysis was based on the published data covering breeding bird communities of 18 lakes in Western Poland. Seven habitat variables were used in the analysis: lake area, length of shore line, maximum depth, area of rushes, length of shoreline covered by emergent vegetation, length of shoreline covered by forest and presence of islands. A stepwise multiple regression analysis revealed that most of the variation in the total bird species richness was explained by the length of shoreline covered by emergent vegetation. The number of water bird species was predicted by the lake area, since the number of reed and bush birds was dependent on the area of rushes. The most important factors determining the total number of pairs were the lake area and the area of rushes. The number of pairs of water birds was dependent on the lake area and the maximum depth. The density of water birds was negatively correlated with the area of rushes and positively with the lake area. The number of pairs of water birds was statistically higher on lakes with islands than on those without. The abundance of reed and bush birds correlated positively with the area of rushes, hence the density was dependent on the maximum depth and the area of rushes. There was no effect of shoreline covered by forest on the abundance of studied groups of birds.
Bibliogr. p. 33-34
P. [27]-35 ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: breeding birds; water birds; waterfowl; Poland; Great Poland (region); Wielkopolska; bird communities; reed and bush birds; lake morphometry; island presence; shore habitat; birds; Aves; 1988-95

Reproduction and feeding success of the red-necked grebe Podiceps grisegena at fish ponds, SE Poland - Kloskowski, Janusz (Muzeum i Instytut Zoologii PAN, 2000)
Investigations were carried out in three fish-pond complexes in 1993-1999. Clutches were initiated 21 April-9 July (mean 11 May). The average clutch size was 3.83 ą 0.44. In total 66.3% breeding pairs reared fledglings (n = 163). The population studied had a higher hatching success (83.4%) compared to data reported in literature but fledging success (1.29 young per breeding, and 1.94 per successful pair) was lower than those documented in Sweden and Russia. 22.3% of dives observed during foraging bouts were successful. Ponds, which seemed suitable for breeding, were less frequently occupied by breeding pairs when stocked after mid-May than ponds stocked earlier. The proportion of nests which produced fledglings was lower in ponds used for recreation than in ponds without such activities. Removal of littoral vegetation using heavy machinery was responsible for destroying of nearly one third of clutches initiated after 15 June.
Referat wygłoszony na Second Meeting of the European Ornithologists' Union
Bibliogr. p. 88
P. [85]-89 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Red-necked Grebe; breeding biology; Poland; congresses; foraging success; breeding success; fish ponds; grebes; birds; Podiceps grisegena; Podicipedidae; Aves

Międzynarodowe sympozjum na temat dzierzb (Lake Placid, Floryda, USA, 11-15 I 1993 r.) - Diehl, Barbara (Państwowe Wydawnictwo Naukowe, 1993)
Pages 257-259 ; 24 cm
Keywords: Laniidae; congresses

Materiały do biologii brzegówki, Riparia riparia (L.) - Wołk, Elżbieta (1938– ) (Państwowe Wydawnictwo Naukowe, 1964)
Liczbowanie stron również: 125-138
Z 3 tabelami w tekście
Bibliogr. p. 12 (136)
14 p. ; 24 cm
Abstracts in Russian, English. Nazwy taksonów także w j. łac.
Keywords: bank swallow; bank martin; sand martin; Poland; Wielkopolska National Park; swallows; birds; Riparia riparia; Hirundinidae; Aves

Analysis of recoveries of same species sugroups with similar potential recovery rates - Jenni, Lukas (Państwowe Wydawnictwo Naukowe, 1987)
Referat wygłoszony na EURING Technical Conference
P. 129-132 ; 24 cm
Keywords: Ptaki -- obrączkowanie -- konferencje [KABA]; bird banding; congresses; methods; birds; Aves

Study on the intersexual differentiation of foraging niche in relation to abundance of winter food in great spotted woodpecker Dendrocopos major - Osiejuk, Tomasz S. (Muzeum i Instytut Zoologii PAN, 1998)
Bibliogr. p. 140-141
P. [135]-141 ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Great Spotted Woodpecker; nutrition; wintering; Poland; Wielkopolska National Park; intraspecific competition; food availability; foraging behaviour; woodpeckers; birds; Dendrocopos major; Picidae; Aves; 1991-93

Nesting ecology of the spotted munia Lonchura punctulata in Mudumalai Wildlife Sanctuary (Southern India) - Gokula, Varadhrajan (Muzeum i Instytut Zoologii PAN, 2001)
The nesting period of the Spotted Munia is from July to November, a period with frequent rains. Built of grass, nests (n = 60) were spherical or dome-shaped, with a lateral entrance-hole oriented mainly along the most frequent wind direction. They were mostly built on twigs within the tree canopy, the majority of them on thorny plant species. The mean depth and diameter of the nests were 12.32 cm and 4.18 cm respectively. Nesting activities were shared by both sexes. Four to six eggs were laid. The incubation period in 17 pairs varied from 10 to 15 days. All the nests (n = 60) were situated on four plant species only, the greatest preference being for Toddalia asiatica (50%), followed by Gymnosporia montana (25%) and Acacia chundra (20%). Although 50% of the nests were found on T. asiatica, this plant is a straggler and no nest was built on it if it was not present in association with G. montana. For constructing nests the Spotted Munia selected short and small trees in a microhabitat with low canopy cover.
Bibliogr. p. 4
P. [1]-5 : ill. ; 27 cm
Abstract in Polish
Keywords: Scaly-breasted Munia; Spotted Munia; breeding biology; breeding ecology; India; nest sites; nesting; estrildid finches; birds; Lonchura punctulata; Estrildidae; Aves

Nesting of the house martin Delichon urbica in the city of Poznań (1976-1978 and 1982-1989) - Ptaszyk, Jerzy (Muzeum i Instytut Zoologii PAN, 2001)
Observations of nesting populations of the House Martin were carried out on three study plots in the city of Poznań: a city centre area (599.0 ha) and two housing estates (567.1 ha and 125.6 ha), a total area of 1291.7 ha. Throughout the 1980s House Martin numbers increased continuously over the whole area, the greatest population density being 4.6 occupied nests per 10 ha. The number of breeding pairs in the city centre was stable, and the density there varied from 2.1 to 3.0 occupied nests per 10 ha. The highest density of occurrence was recorded in the new housing estates, where increases in the House Martin population were recorded. These was related to the construction of new buildings, which provided fresh nesting sites. The nests were built at heights from the first to the fifteenth storey. Over 96% of the nests in the housing estates were built in the corners of the window openings. In the entire study area the preferred nesting sites were on the southern (35.2%), northern (26.1%) and eastern (13.3%) sides of buildings. In the city centre the greatest number of nests had south-facing entrances, while in one of the other study plots, the entrances to most nests faced north. No more than 7% of the total number of martins' nests available in a given year were occupied by Passer domesticus.
Bibliogr. p. 140-141
P. [135]-142 : ill. ; 27 cm
Abstract in Polish
Keywords: House Martin; breeding biology; Poland; Poznań; population dynamics; urban habitats; nest sites; nesting biology; swallows; birds; Delichon urbica; Hirundinidae; Aves; 1976-78; 1982-89

Habitat preferences of foraging rooks Corvus frugilegus during the breeding period in the agricultural landscape of eastern Poland - Kasprzykowski, Zbigniew (Museum & Institute of Zoology, 2003)
The study was carried out in 2000-2002 around 6 rookeries. Rooks foraged in numbers from 1 to 132 birds (n = 417); flocks of less than 10 individuals were dominant. The type of crop influenced the size of a foraging flock. Most of the rooks were recorded within 0.5-1 km of the rookery, while the greatest distance of a foraging ground from the rookery (>> = 2833.3 m) depended on the size of that rookery. Spring corn, meadows and pastureland were of the greatest significance in the rooks foraging area. Winter corn and root crops were avoided, while wasteland areas were visited intermittently.
Bibliogr. p. 30
P. [27]-31 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Rook; birds; Poland; Siedlce; foraging preferences; agricultural landscape; Corvus frugilegus; Corvidae; Aves; 2000-2002